Binding specificities of estrogen receptor with perfluorinated compounds: A cross species comparison. (January 2020) - Qiu, Zhiqiang; Qu, Kaili; Luan, Feng; Liu, Yaquan; Zhu, Yu; Yuan, Yongna; Li, Hongyu; Zhang, Haixia; Hai, Ying; Zhao, Chunyan
Highlights: The cross-species comparison of PFCs is important for health risks evaluation. In vivo and in vitro experiments explored cross-species comparison of PFCs to ER. PFCs presented more sensitive to human ER than to rats ER. Molecular dynamic is powerful to in silico predict species difference of PFCs to ER. Abstract: Background: Perfluorinated compounds (PFCs) were reported to result in the endocrine disruption by activating the estrogen receptor (ER) and inducing ER-mediated transcriptions. Objective: The aim of the present work was to perform cross-species comparisons on the characteristics of eight PFCs binding to humans ERα and to rats ERα. Methods: In the present work, in vivo tests, including serum estradiol level assay and immunohistochemical staining, fluorescence assay and molecular models were applied. Results: Based on the in vivo experiments, the exposure of PFOA and PFOS to female rats was proved to increase the ERα expression in the terus, suggesting that PFCs may act as estrogenic compounds to activate ERα in vivo . The further fluorescence assay presented that these eight PFCs have stronger binding abilities to human ERα than to rat ERα. In addition, the differences in binding specificities between human ERα and rat ERα were identified in the process of molecular dynamics modeling with the term of helix position and the ability of coregulator recruitment. It can be found that more and stronger charge clamps could form between PFCs with human ERα than with rat ERα. Also, the eight PFCs presented lower binding energies in human ERα systems, which proved that eight PFCs presented much stronger binding abilities with human ERα. Discussion: In all, it can be concluded that PFCs might be more sensitive to human ERα than to that of rats, which also suggested the greater susceptibility to adverse effects on humans. The present work was a beginning assessment of a cross-species comparison, providing important information on health impacts of PFCs in humans.